Characteristics and mechanism of karst groundwater cycle evolution under large-scale exploitation: a case study of the Yanxi karst groundwater system - Yawei Feng; Fengxin Kang; Fengfeng Shi; Xuesen Wang; Xianzhou Meng; Yifu Fu; Aijun Li; Hao Chen; Qingcheng He (Carbonates and Evaporites, 2026)

Isolation and identification of tropical source Lactobacillus plantarum CK3 and its effects on fatty liver in laying hens - Yongzhen Chen; Xinyu Feng; Xinyi Zhang; Andrea Abreo Medina; Jiayu Feng; Xin Li; Meiyu Duan; Yawei Qiu; Fang Gan (Research in Veterinary Science, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

Multi-mode and encapsulated droplet-based electricity generator for environmental sensing and cathodic protection - Miaomiao Cui; Peiyu Wu; Ruiqi Fang; Wenbo Zhao; Yuankai Jin; Yawei Feng; Fuhui Wang; Zhipeng Zhang; Xiangyu Li; Dake Xu (Chemical Engineering Journal, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

Prenatal Chromium Exposure and Gestational Diabetes Mellitus: Integrating Genetic and Epigenetic Regulation of LPCAT1 from a Phospholipid Remodeling Perspective - Yuxin Tian; Lu Yao; Jiaqi Zhang; Meng Zhou; Yue Dou; Bole Zhang; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang; Weiwei Wu (Biological Trace Element Research, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Untargeted metabolomics-based investigation of amino acid effects on antimicrobial peptides production in Paenibacillus ehimensis HD 8-3 fermentation - Chengling Feng; Jiapei Zhang; Yunfei Si; Zhen Zhao; Yawei Ning; Zhixin Wang (Food Bioscience, 2026)

Nutrient recovery from source-separated urine and urease inhibition during evaporation by a combination of salt, absorbent material, and dehumidification - Weikun Chen; Huijun Xiang; Chun Chen; Lanyue Feng; Ke Bei; Yawei Liu; Min Zhao; Xiangyong Zheng (Chemical Engineering Journal, 2026)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Radical and non-radical peroxymonosulfate activation induced by a novel ferromagnetic Fe1-xS/lignin-based biochar nanocomposite: Multi-pathway synergistic effects for bisphenol A removal - Minglu Zhang; Zunqing Wen; Longquan Zhang; Qingyun Wang; Lihua Zang; Qing Feng; Yawei Gu; Wenyu Wang; Ke Ma; Hao Zhang; Dandan Ji; Jun Liu; et al. (Chemical Engineering Journal, 2025)

Mediating role of whole epigenome DNA methylation signatures in the association between copper and SGA - Weiwei Wu; Mengru Wang; Shan Li; Bole Zhang; Weixuan Hu; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang (Journal of Trace Elements in Medicine and Biology, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

The Combined Effect Between SEPS1 Genetic Polymorphisms and Exposure to Metals on the Risk of Gestational Diabetes Mellitus - Weiwei Wu; Yulin Li; Weixuan Hu; Jing Zhao; Bole Zhang; Yongliang Feng; Yawei Zhang; Suping Wang (Biological Trace Element Research, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Impact of surface reservoir construction on groundwater circulation and recharge in the Yangzhuang karst groundwater system, China - Yawei Feng; Fengxin Kang; Bintao Liu; Lichuan Zhang; Zhifeng Li; Xuetao Xing; Qingcheng He (Hydrogeology Journal, 2025)

The weak association between hypoxia tolerance and thermal tolerance increases the susceptibility of abalone to climate change - Yawei Shen; Yue Dai; Feng Yu; Wenzhu Peng; Junyu Liu; Weiwei You; Xuan Luo; Caihuan Ke; Nan Chen (Environmental Research, 2025)

Evolution of hydrochemistry and water quality of karst groundwater under the effects of intense anthropogenic activities - Yawei Feng; Fengxin Kang; Yongli Guo; Zhifeng Li; Bintao Liu; Hongzhi Bu; Chunying Xia; Qingcheng He (Journal of Environmental Management, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

A review of the pollution signatures of polycyclic aromatic hydrocarbons in the sediments of the East China Sea - Fang Yin; Chen Gao; Daolun Feng; Yawei Sun (Environmental Pollution, 2024)

Antifungal mechanism of Lactiplantibacillus plantarum P10 against Aspergillus niger and its in-situ biopreservative application in Chinese steamed bread - Mengge Ma; Ao Li; Jin Feng; Zhixin Wang; Yingmin Jia; Xinying Ma; Yawei Ning (Food Chemistry, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Domestication affects nitrogen use efficiency in foxtail millet - Yufeng Deng; Yawei Chen; Taiji Kou; Yukun Bo; Meicheng Zhao; Feng Zhu (Euphytica, 2024)

TREM2 Deficiency Aggravates NLRP3 Inflammasome Activation and Pyroptosis in MPTP-Induced Parkinson’s Disease Mice and LPS-Induced BV2 Cells - Peiting Huang; Zhanyu Zhang; Piao Zhang; Jiezhu Feng; Jianwei Xie; Yinjuan Zheng; Xiaomei Liang; Baoyu Zhu; Zhenzhen Chen; Shujun Feng; Lijuan Wang; Jiahong Lu; et al. (Molecular Neurobiology, 2024)
Microglia-mediated neuroinflammation plays a crucial role in the pathogenesis of Parkinson’s disease (PD). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effects in PD by regulating the phenotype of microglia. Recent studies suggest that TREM2 regulates high glucose-induced microglial inflammation through the NLRP3 signaling pathway. This study aimed to investigate the effect of TREM2 on NLRP3 inflammasome activation and neuroinflammation in PD. Mice were injected with AAV-TREM2-shRNA into both sides of the substantia nigra using a stereotactic injection method, followed by intraperitoneal injection of MPTP to establish chronic PD mouse model. Behavioral assessments including the pole test and rotarod test were conducted to evaluate the effects of TREM2 deficiency on MPTP-induced motor dysfunction. Immunohistochemistry of TREM2 and tyrosine hydroxylase (TH), immunohistochemistry and immunofluorescence Iba1, Western blot of NLRP3 inflammasome and its downstream inflammatory factors IL-1β and IL-18, and the key pyroptosis factors GSDMD and GSDMD-N were performed to explore the effect of TREM2 on NLRP3 inflammasome and neuroinflammation. In an in vitro experiment, lentivirus was used to interfere with the expression of TREM2 in BV2 microglia, and then lipopolysaccharide (LPS) and adenopterin nucleoside triphosphate (ATP) were used to stimulate inflammation to construct a cellular inflammation model. The expression differences of NLRP3 inflammasome and its components were detected by qPCR and Western blot. In vivo, TREM2 knockdown aggravated the loss of dopaminergic neuron and the decline of motor function. After TREM2 knockdown, the number of activated microglia was significantly increased, and the expression of cleaved caspase-1, NLRP3 inflammasome, IL-1β, GSDMD, and GSDMD-N was increased. In vitro, TREM2 knockdown aggravated the inflammatory response of BV2 cells stimulated by LPS and promoted the activation of NLRP3 inflammasome through the NF-κB pathway. In addition, TREM2 knockdown also promoted the expression of TLR4/MyD88, an upstream factor of the NF-κB pathway. Our vivo and vitro data showed that TREM2 knockdown promoted NLRP3 inflammasome activation and downstream inflammatory response, promoted pyroptosis, and aggravated dopaminergic neuron loss. TREM2 acts as an anti-inflammatory in PD through the TLR4/MyD88/NF-κB pathway, which extends previous findings and supports the notion that TREM2 ameliorates neuroinflammation in PD.

New insights into Co3O4-carbon nanotube membrane for enhanced water purification: Regulated peroxymonosulfate activation mechanism via nanoconfinement - Huanran Ma; Guoqing Feng; Xiao Zhang; Chengwen Song; Ruisong Xu; Yawei Shi; Pengcheng Wang; Zhouhang Xu; Guanlong Wang; Xinfei Fan; Zonglin Pan (Chemosphere, 2024)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

Research on the risk evaluation of urban wastewater treatment projects based on an improved fuzzy cognitive map - Hongyu Chen; Jingyi Wang; Zongbao Feng; Yang Liu; Wen Xu; Yawei Qin (Sustainable Cities and Society, 2023)

3D reconstruction of plants using probabilistic voxel carving - Jiale Feng; Mojdeh Saadati; Talukder Jubery; Anushrut Jignasu; Aditya Balu; Yawei Li; Lakshmi Attigala; Patrick S. Schnable; Soumik Sarkar; Baskar Ganapathysubramanian; Adarsh Krishnamurthy (Computers and Electronics in Agriculture, 2023)

Prenatal polymetallic exposure and small for gestational age: A case-control study in Taiyuan, China - Zhitong Shen; Yue Lu; Zexin Song; Jinbo Li; Wangjun Li; Shan Li; Mengru Wang; Yongliang Feng; Suping Wang; Yawei Zhang; Weiwei Wu (Journal of Trace Elements in Medicine and Biology, 2023)

Bioleaching performance of vanadium-bearing smelting ash by Acidithiobacillus ferrooxidans for vanadium recovery - Xiaoxiao Guo; Siming Chen; Yawei Han; Chunbo Hao; Xiujuan Feng; Baogang Zhang (Journal of Environmental Management, 2023)

Efficient anti-frosting on discrete nanoclusters via spatiotemporal control of condensation frosting dynamics - Siyan Yang; Yushan Ying; Wanbo Li; Yawei Feng; Rongfu Wen; Qixun Li; Yuanbo Liu; Bingang Du; Zuankai Wang; Xuehu Ma (Chemical Engineering Journal, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Highly reactive coke made from Low-rank Coal: Relationship between thermal properties and multilevel structure - Xin Zhang; Jun Zhang; Rui Guo; Qiang Xiao; Yawei Feng; Huan Cheng (Fuel, 2023)

Exploring the mechanism of Chaihujia Longgu Muli decoction in the treatment of epilepsy in rats based on the RhoA/ROCK signaling pathway - Gang Feng; Xianghua Liu; Baoying Wang; Ruixing Li; Yaxin Chang; Nannan Guo; Yawei Li; Tiantian Chen; Bingxiang Ma (Molecular Biology Reports, 2023)

Bond behavior of an ultra-high performance concrete-filled anchorage for carbon fiber-reinforced polymer tendons under static and impact loads - Yawei Fang; Zhi Fang; Lixin Feng; Yu Xiang; Xuhong Zhou (Engineering Structures, 2023)

Variations of human cerebral and ocular blood flow during exposure to multi-axial accelerations - Weipeng Li; Bitian Wang; Yawei Wang; Xiaoyu Liu; Wentao Feng; Tianya Liu; Zhujun Sun; Yu Liu; Songyang Liu; Yubo Fan (Medical & Biological Engineering & Computing, 2022)

Fluctuations in the heart rate of abalone in response to low salinity stress - Grace Afumwaa Boamah; Feng Yu; Yawei Shen; Weiwei You; Changan Xu; Xuan Luo; Caihuan Ke (Aquaculture International, 2022)

Enterobacter sp. FM-1 inoculation influenced heavy metal-induced oxidative stress in pakchoi (Brassica campestris L. ssp. Chinensis Makino) and water spinach (Ipomoea aquatic F.) cultivated in cadmium and lead co-contaminated soils - Fangming Yu; Yawei Yao; Jingpei Feng; Xueru Wang; Jiangming Ma; Kehui Liu; Yi Li (Plant and Soil, 2021)

The differential expression of novel circular RNAs in an acute lung injury rat model caused by smoke inhalation - Zhiqiang Ye; Xuhui Liu; Yuewu Yang; Xianling Zhang; Ting Yu; Shigeng Li; Yawei Feng; Gangjian Luo (Journal of Physiology and Biochemistry, 2018)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Variation of phytoplankton functional groups modulated by hydraulic controls in Hongze Lake, China - Chang Tian; Haiyan Pei; Wenrong Hu; Daping Hao; Martina A. Doblin; Ying Ren; Jielin Wei; Yawei Feng (Environmental Science and Pollution Research, 2015)

Spatiotemporal distribution pattern of cyanobacteria community and its relationship with the environmental factors in Hongze Lake, China - Ying Ren; Haiyan Pei; Wenrong Hu; Chang Tian; Daping Hao; Jielin Wei; Yawei Feng (Environmental Monitoring and Assessment, 2014)

Calcineurin Plays an Important Role in the Shell Formation of Pearl Oyster (Pinctada fucata) - Changzhong Li; Yilin Hu; Jian Liang; Yawei Kong; Jing Huang; Qiaoli Feng; Shuo Li; Guiyou Zhang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2010)